1990
DOI: 10.1016/0014-5793(90)81420-s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rat brain NCAM mRNA using DNA oligonucleotide probes

Abstract: Neural cell adhesion molecule; Northern blotting; Oligonucleotide A number of different isoforms of the neural cell adhesion molecule (NCAM) have been identified. The difference between these is due to alternative splicing of a single NCAM gene. In rat brain NCAM mRNAs with sizes of 7.4, 6.7, 5.2, 4.3 and 2.9 kb have been reported. We have synthesized six DNA oligonucleotides, that hybridize to different exons in the NCAM gene. Furthermore we have constructed three oligonucleotides, that exclusively hybridize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This is possibly due to a very low turnover of this polypeptide in BT4C cells or, alternatively, due to a higher sensitivity of the blotting technique. In some Northern blots we observed a low amount of the 7.4-kb NCAM mRNA, which encodes the 190,000 (NCAM-A) polypeptide (Barthels et al, 1988;Anderson et al, 1990). There have been doubts whether astroglial cells produce the 190,000 (NCAM-A) form or not.…”
Section: Discussionmentioning
confidence: 88%
“…This is possibly due to a very low turnover of this polypeptide in BT4C cells or, alternatively, due to a higher sensitivity of the blotting technique. In some Northern blots we observed a low amount of the 7.4-kb NCAM mRNA, which encodes the 190,000 (NCAM-A) polypeptide (Barthels et al, 1988;Anderson et al, 1990). There have been doubts whether astroglial cells produce the 190,000 (NCAM-A) form or not.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, a direct action of PIPLC may be prevented by steric hindrance, e.g., due to clustering of GPI-linked molecules at the prostasome membrane surface, or their sequestration in invaginated membrane regions [24], or their modification through acylation of an inositol hydroxy-group by a fatty acid as has been reported for the ectoenzyme acetylcholinesterase of human erythrocytes [25]. Another possibility might be that the prostasome membrane-associated protein exists in two forms, one is GPI-anchored and the other is not as demonstrated for neural cell adhesion molecule [26] and the IgG receptor, F, , RIII (CD16) [27]. It has been reported that GPI-anchored proteins are poorly solubilized by nonionic detergents like Triton X-100 [8,28].…”
Section: Discussionmentioning
confidence: 99%
“…ST8Sia II, and NCAM in postnatal rat brain development Northern blot analysis was carried out with poly (A) + RNA isolated from whole brains of postnatal rats at the age of 2 days [postnatal day (P) 2], P21, and 6 months. The NCAM probe developed the known hybridization pattern with bands of 7.4, 6.7, 5.2, and 2.9 kb (Andersson et al, 1990;Linnemann et al, 1993) (Fig. 1).…”
Section: Changes In Expression Level Of St8sia IVmentioning
confidence: 99%